Reviving Troost: Using Phytotechnology to Decontaminate Troost Avenue's Vacant lots - Belk, Ayana (Kansas State University. K-State Libraries, 2018)
Kansas City is a divided city, split along its north-south axis by Troost Avenue. Most African-American residents live on the east side of Troost, while on the west side are primarily white and upper-middle class residents. Troost Avenue was once an attractive and desirable place to have a business. Today, the street is run-down, with many vacant lots and buildings and exclusively serves as an artery of the local bus route. My aim is to find a way to improve Troost’s streetscape in an attempt to unify the city aesthetically and culturally. The question that drives this project is: What design interventions could bring Troost Avenue back to being an asset for the community? To answer this, I have done archival research at Kansas State University and the Kansas City Public Libraries to better understand the role of Troost Avenue in the past. I have also delved into the world of phytotechnology via the book Phyto: Principles and Resources for Site Remediation and Landscape Design. Phytotechnology is a design tool that uses vegetation to contain or prevent the movement of contaminants in soils, sediments and groundwater. With this information I am proposing a demonstration neighborhood park at the corner of Troost and Linwood to show how the existing vacant lots could be improved to better meet the expectations of the community. This entails documentation of the current conditions of the street and a proposed design for improvements.
Citation: Belk, A. (2018) How Hale helped me Revive Troost. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Freshman Category, grand prize